Sources of economically valuable traits for winter triticale breeding in the northwest of the Russian Federation - V. A. Uspenskaja; L. P. Bekish; N. N. Chikida (Труды по прикладной ботанике, генетике и селекции)
Background. As a crop, triticale is an important source that can be used to meet the growing needs of animal husbandry in high-quality feeds and of the population in organic products. Triticale combines the high productivity potential of wheat with high adaptability of rye. However, the expansion of triticale production in the Northwestern Region of the Russian Federation is hindered by the unresolved breeding and genetic problems, like tendency to lodging, sprouting in the ear, unstable productivity and insufficient disease resistance. In this regard, the further development of breeding in the Russian Northwest depends on studying the triticale gene pool and synthesis of original initial material for the creation of new high-yielding varieties.Material and methods. Field and laboratory studies were conducted at the experimental base of the "BELOGORKA" Leningrad Research Institute. The experimental design and statistical data processing followed the standard technique. Phenological observations, field and laboratory assessments were carried out according to the standard methods.Results and conclusion. The three-year study (2015-2017) of the winter triticale collection material of different ecogeographic origin has resulted in the identification of genetic sources of individual important agronomic traits, such as early maturity (e.g., 'Don' (k-3637), 'Almaz' (k -3908), 'Proryv' (k-3763), 'Interes' (k-3968), 'Pshenichnoe' (k-3965), 'ADM-6' (k -3544), 'ADM-9' (k-3421), 'Utro' (k-3926)), dwarfness (e.g., 'Ramzaj' (k-4071), 'Samurai' (k-4072), 'Skif' (k-3931), 'Zavet' (k-4020), 'Proryv' (k-3763), 'Dozor' (k-4021), 'Knyaz'' (k-4076),    'L-372'    (k-2806), 'Pshenichnoe' (k-3965), 'Kroha' (k-3929)), productivity (e.g., 'Impul's' (k- 3999), 'Prometey' (k-3900), 'Kvazar' (k-3938), 'Interes' (k-3968), 'Trizub' (k-3969), 'Papsuevskaya' (k-3924), 'Svityaz'' (k-3963), 'Topaz' (k-3909), 'Dawitol' (k-4002), 'Prado' (k-3865)), and disease resistance (e.g., 'PRAG 536' (k-3945), 'PRAG 456' (k-3946), 'Kvazar' (k-3938), 'Prometey' (k- 3900), 'Svyatozar' (k-3940), 'Yasha' (k-3912)). The accessions with a set of important traits that have been selected as the initial material for breeding winter triticale in the Northwest of the Russian Federation include 'Topaz' (k-3909), 'Don' (k-3637) 'Trizub' (k-3969), 'Interes' (k- 3968), 'Pshenichnoe' (k-3965), 'Svityaz'' (k-3963), 'Amulet' (k- 3956), 'Impul's' (k-3999), 'Kvazar' (k-3938), and 'Dawitol' (k-4002). The lines [(Niklap x Antei) x L-21620] x Fidelio and (Niklap x Antei) x ADM-9 have been identified as two promising lines with a complex of economically valuable traits.